Coronary CT angiography in clinical triage of patients at high risk of coronary artery disease. (2nd January 2017) - Kühl, J. Tobias; Hove, Jens D.; Kristensen, Thomas S.; Norsk, Jakob B.; Engstrøm, Thomas; Køber, Lars; Kelbæk, Henning; Kofoed, Klaus F.
Abstract: Objectives . To test if cardiac computed tomography angiography (CCTA) can be used in the triage of patients at high risk of coronary artery disease. Design . The diagnostic value of 64-detector CCTA was evaluated in 400 patients presenting with non-ST segment elevation myocardial infarction using invasive coronary angiography (ICA) as the reference method. The relation between the severity of disease by CCTA and a combined endpoint of death, re-hospitalization due to new myocardial infarction, or symptom-driven coronary revascularization was assessed. Results . CCTA detects significant (>50%) coronary artery diameter stenosis with a sensitivity, specificity, and positive and negative predictive value of 99%, 81%, 96% and 95%, respectively. CCTA was used to triage patients into guideline defined treatment groups of "no or medical treatment", "referral to percutaneous coronary intervention" or to "coronary artery bypass graft surgery" and was compared to the index ICA. CCTA correctly triaged patients in 86% of cases. During a median follow-up of 50 months, the presence of an occluded artery by CCTA was associated with adverse outcome. Conclusion . CCTA has high diagnostic and prognostic value in patients with high likelihood of coronary artery disease and could, in theory, be used to triage high risk patients. As many obstacles remain, including logistical and safety issues, our study does not support the use of CCTA as an additional diagnostic test before ICA in an all-comer NSTEMI population.